The Tales of Three Kongs of Sarawak - Chai, Elena Gregoria Chin Fern (Sarawak Chinese Cultural Association, 2021)
Belief in Tua Pek Kong (大伯公), Tu Di Kong (土地公) and Datuk Kong (拿督公) is among the distinctive features of Chinese folk beliefs in Sarawak. In almost every town in Sarawak is a temple dedicated to Tua Pek Kong, also known as Fu De Zheng Shen (福德正神). There are Tu Di Kong in temples and also cemeteries, while Datuk Kong guards temples, oil palm plantations, timber camps and similar places. These deities share a commonality: they maintain a tutelary relationship with the local worshippers. Fieldwork was conducted in a Hakka village from 2008 to 2009 and visits were made to all Tua Pek Kong temples in Sarawak in 2013. This paper presents partial findings on the relationship between Tua Pek Kong, Tu Di Kong and Datuk Kong. The deities’ functions in specific localities are described. It is hoped that the ethnographic data presented here shall help in the understanding of these three tutelary deities in Sarawak and West Malaysia. Folk beliefs are local constructs to accommodate communities’ needs. Differences in worship or differences in the functions of the deities are some unique characteristics of folk beliefs.